2006
DOI: 10.1007/s00520-006-0090-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential levels of stress in caregivers of brain tumor patients—observations from a pilot study

Abstract: Caregivers of patients with BT experience significant stress. Furthermore, this data provide an indication of the profound levels of stress these caregivers experience. Caregivers of patients with grade I/II tumors are at increased risk for experiencing stress. Younger caregiver age and higher levels of education were also found to correlate to higher levels of stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 25 publications
0
33
0
1
Order By: Relevance
“…Actually, Janda et al [38] found a trend for lower quality of life among caregivers that looked after patients with high-grade disease. However, other research reported that caregivers of patients with grade I/II tumors were more stressed than their grade III/IV counterparts [39]. A possible explanation for these discrepant results is that a diagnosis of brain tumor leads to a life in which the perception of ''incurable disease'' prevails, as compared with ''high-or low-grade disease.…”
Section: Discussionmentioning
confidence: 94%
“…Actually, Janda et al [38] found a trend for lower quality of life among caregivers that looked after patients with high-grade disease. However, other research reported that caregivers of patients with grade I/II tumors were more stressed than their grade III/IV counterparts [39]. A possible explanation for these discrepant results is that a diagnosis of brain tumor leads to a life in which the perception of ''incurable disease'' prevails, as compared with ''high-or low-grade disease.…”
Section: Discussionmentioning
confidence: 94%
“…Providing care to a person with a PMBT involves managing cognitive and physical deficits that become worse throughout the trajectory. Caregivers typically are older female spouses (Cashman et al, 2007; Keir et al, 2006; Muñoz et al, 2008; Salander & Spetz, 2002; Schmer, Ward-Smith, Latham, & Salacz, 2008; Sherwood, Given, Doorenbos, & Given, 2004; Sherwood et al, 2006, 2007; Wideheim, Edvardsson, Påhlson, & Ahlström, 2002). Few studies of caregivers of individuals with a PMBT exist and, although reports of sleep disturbances have been noted, no studies of sleep have been reported in this unique caregiving population.…”
mentioning
confidence: 99%
“…Caregivers experienced increased symptoms of depression, anxiety, psychosomatic symptoms, strain in intimate relationships, and diminished physical health. 9,20,28 As expected, patients' functional status was correlated with caregivers' QoL. Caregivers of glioma patients with a loss of independence reported more burden than caregivers of patients with good scores for performance status.…”
Section: Discussionmentioning
confidence: 48%
“…Indeed, patients' QoL depends in part upon the availability of support and the capacity of the caregiver. 16,17 Caregivers of patients with brain tumors are considered a unique subset of the cancer caregiver population, 18 and issues related to QoL are very important to them 19 because of the challenges they have to confront in caring for a loved one who is suffering from a disease with a potentially short terminal trajectory and severe functional, 20 cognitive, and neuropsychological sequelae 21 that produce major changes in their lifestyle. 16 The QoL of glioma caregivers is expected to be more disrupted than that of any other oncology caregivers.…”
mentioning
confidence: 99%